Floors number influence on the instability parameter of reinforced concrete wall- or core-braced buildings - Ellwanger,R. J. (2013)
This work aims to investigate the floors number influence on the instability parameter limit α1 of buildings braced by reinforced concrete walls and/or cores. Initially, it is showed how the Beck and König discrete and continuous models are utilized in order to define when a second order analysis is needed. The treatment given to this subject by the Brazilian code for concrete structures design (NBR 6118) is also presented. It follows a detailed analytical study that led to the derivation of equations for the limit α1 as functions of the floors number; a series of examples is presented to check their accuracy. Results are analyzed, showing the precision degree achieved and topics for continuity of research in this field are indicated.